Web standards creativity innovations in web design with XHTML, CSS, and DOM scripting - Adams, Cameron (Apress, 2007)
Web Standards Creativity is the ultimate in inspirational, high-level web design books an innovative book for the very successful but highly contested web standards market. There is no attempt to teach the basics CSS or JavaScript competency is already assumed. This book brings together 12 of the world's most talented web designers (including Andy Budd, Andy Clarke, Ethan Marcotte, Simon Collison, and Ian Lloyd,) all renowned in the web design community, and many of them already proven authors, to share their secrets with the reader. The techniques discussed cover the full spectrum of essential web design topics, but not run of the mill content readers will find enough innovation inside that they will keep coming back to the book again and again to improve their work. The book is completely standards-compliant, and up-to-date, including discussions of IE 7 support. And to make learning even more rewarding, the book is presented in glorious full color.